Improving Writing Fluency through Free Writing Activities: An Experimental Study - Rizqi Claudia Wardani; La Sunra; Syarifuddin Dollah (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
Writing fluency is an important aspect of English learning, yet many EFL students struggle to produce continuous and coherent texts because of anxiety, limited vocabulary, and a strong focus on accuracy. This study aims to examine whether free writing activities can improve students’ writing fluency. A quasi-experimental design was used with two groups: an experimental group that received free writing treatment and a control group taught through conventional writing methods. Writing fluency was measured through pre- and post-tests focusing on speed, flow of ideas, and coherence. Data were analyzed using paired-sample and independent-sample t-tests. The results show that the experimental group made significant gains in writing fluency, producing longer and more connected texts, while the control group showed only slight improvement. These findings indicate that free writing is an effective strategy for reducing anxiety and encouraging continuous idea expression. Overall, the study highlights the value of fluency-oriented activities in strengthening students’ writing competence.